To solve the equation \(-91 + z = 97\), follow these steps:
-
Start with the equation:
\(-91 + z = 97\) -
Add 91 to both sides to isolate \(z\):
\(-91 + z + 91 = 97 + 91\)
This simplifies to:
\(z = 188\)
So, the solution is:
\(z = 188\)
−91+z=97-91+z=97−91+z=97
z=z=z=
1 answer
To solve the equation \(-91 + z = 97\), follow these steps:
Start with the equation:
\(-91 + z = 97\)
Add 91 to both sides to isolate \(z\):
\(-91 + z + 91 = 97 + 91\)
This simplifies to:
\(z = 188\)
So, the solution is:
\(z = 188\)